Pacific Climate Cultures Living Climate Change in Oceania - Crook, Tony (De Gruyter, 2019)
This edited volume examines the opportunities to think, do, and/or create jointly afforded by digital storytelling. The contributors discuss digital storytelling in the context of educational programs, teaching anthropology, and ethnographic research involving a variety of populations and subjects that will appeal to researchers and practitioners engaged with qualitative methods and pedagogies that rely on media technology.